EVALUATION OF APOLIPOPROTEIN-B LEVELS IN DYSGLYCEMIA - POONGUZHALI.D.V; VINODHINI.V.M; WILLIAM.W, EBENEZER; KUMAR.J.S (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Lifestyle modifications have resulted in an increased prevalence of dysglycemia in young individuals. Impaired Fasting Glucose (IFG) and Impaired Glucose Tolerance (IGT) represent intermediate stages of abnormal glucose regulation that exists between normal glucose homeostasis and diabetes. IFG is considered as a potential indicator of preventive importance for diabetes and cardiovascular diseases. The plasma concentration of apolipoprotein B (apo B) indicates the cumulative number of atherogenic particles. The study group included 50 patients with IFG and 50 euglycemic subjects in the age group of 20-35 years. Apo-B and lipid profile measurements were carried out. As compared to the euglycemic group, in the dysglycemic group the Body Mass Index (BMI) and apo-B levels were significantly elevated while there was no significant difference in Low Density Lipoprotein-Cholesterol (LDL-C) levels. The inclusion of apo-B in atherogenic risk assessment will be beneficial for early identification and intervention strategies. Keywords: Dysglycemia, Impaired Fasting Glucose, apolipoprotein-B.